IMPLEMENTASI AKAD SYIRKAH DALAM PROGRAM Z-CHICKEN UNTUK PEMBERDAYAAN EKONOMI MUSTAHIK BAZNAS JEMBER - Halili halili; Firman Yusril Bakhtiar; M David Maulana; M Hasyim Asy’ari (KASBANA, 2025)
This study discusses the implementation of the syirkah agreement in the Z-Chicken program managed by BAZNAS Jember as a form of economic empowerment for mustahik. A syirkah agreement is a form of cooperation between two or more parties to share capital, labor, or expertise in order to run a business with an agreed distribution of profits. The syirkah agreement is used as the basis for cooperation between BAZNAS Jember as the investor and mustahik as the business manager. This program aims to increase the economic independence of mustahik through a fast food fried chicken business by providing business capital, training, and assistance. This study employs a qualitative approach with a descriptive method. Data was collected through primary and secondary sources, including observation, interviews, and documentation. The results indicate that the implementation of the syirkah agreement in this program aligns with Sharia principles such as fairness, transparency, and sustainability. However, there are challenges in its implementation, such as beneficiaries' lack of experience in managing businesses and market access challenges. Despite this, the program has had a positive impact on increasing beneficiaries' income and economic independence. The Z-Chicken program serves as an innovative model for productive zakat with promising potential for the future. To enhance the program's effectiveness, intensive mentoring, market access expansion strategies, and regular evaluations are needed to optimize the results achieved. Keywords: Productive Zakat, Syirkah Agreement, Z-Chicken, BAZNAS